MANAJEMEN KOMUNIKASI PEMERINTAH DAERAH DALAM PROGRAM PEMBERDAYAAN MASYARAKAT (Studi Manajemen Komunikasi Program Bela dan Beli Kulon Progo di Kulon Progo, Yogyakarta - , Ria Harlinawati; , Dr. Kuskridho Ambardi, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The success of community empowerment program is highly dependent on the government's communication strategy to implement sosialization effectively and accurately targeted. At this time, the government of Kulon Progo to prioritize the transparency of information to allow monitoring by the public to government programs. Thatâs why Bela dan Beli Kulon Progo program appears to be a most popular governmentâs program than other government programs among the public, especially the people of Kulon Progo. The purpose of this research is to determine how the communication management methods of Bela dan Beli Kulon Progo implemented by the government of Kulon Progo so this program can reduce apathy towards government programs that have been there within the community, especially the people of Kulon Progo. Type of this research is a qualitative descriptive research using a case study approach. Objects in this research is the government of Kulon Progo with research subjects are primary informants and secondary informants. Method of communication management discussed with the four-step method of management Cutlip, Center, and Broom. This results of this research have found that government communication method by the government of Kulon Progo government by performing four step, including define a problem, communication planning, action and communication, and evaluation of communication. But it has not been implemented to the maximum, so that the results are only a maximum on the cognitive effects , whereas the affective and conative effects are far from optimal.